Data analytics in marketing, entrepreneurship, and innovation - Kehal, Mounir; El Alfy, Shahira (Boca Raton, FL ; Oxon : CRC Press, 2021)
Innovation based in data analytics is a contemporary approach to developing empirically supported advances that encourage entrepreneurial activity inspired by novel marketing inferences. Data Analytics in Marketing, Entrepreneurship, and Innovation covers techniques, processes, models, tools, and practices for creating business opportunities through data analytics. It features case studies that provide realistic examples of applications. This multifaceted examination of data analytics looks at: Business analytics Applying predictive analytics Using discrete choice analysis for decision-making Marketing and customer analytics Developing new products Technopreneurship Disruptive versus incremental innovation The book gives researchers and practitioners insight into how data analytics is used in the areas of innovation, entrepreneurship, and marketing. Innovation analytics helps identify opportunitiesto developnew products and services,and improveexisting methods of product manufacturing and service delivery. Entrepreneurial analytics facilitates the transformation of innovative ideas into strategy and helps entrepreneurs make critical decisions based on data-driven techniques. Marketing analytics is used in collecting, managing, assessing, and analyzing marketing data to predict trends, investigate customer preferences, and launch campaigns.
OCLC-licensed vendor bibliographic record.
Keywords: Business intelligence -- Data processing; Marketing -- Data processing; Entrepreneurship -- Data processing; COMPUTERS / Database Management / Data Mining; BUSINESS & ECONOMICS / Management Science; COMPUTERS / Information Technology